Pengaruh Viral Marketing dan Harga Terhadap Perilaku Impulse Buying Pada Market Place Shopee (Studi Pada Mahasiswa Pasca Sarjana Universitas Lambung Mangkurat) - Anggraini, Nabilah Tri; Irwansyah, Irwansyah (Universitas Lambung Mangkurat, 2023)
The purposes of this study were 1) to determine and test the partially significant effect of viral marketing on impulse buying at the marketplace place shopee (Study on Postgraduate Students at Lambung Mangkurat University), 2) to determine and test the partially significant effect of price on impulse buying at the marketplace marketplace (Study on Post-Graduate Students at Lambung Mangkurat University), 3) to determine and test the significant effect simultaneously of viral marketing and price on impulsive purchases at market place marketplaces (Study on Postgraduate Students at Lambung Mangkurat University).The type of research used is explanatory. The population in this study were Postgraduate Students at Lambung Mangkurat University with a total sample of 190 people. Methods of data analysis using multiple linear regression analysis. The results of the study show that 1) there is a partial significant effect of viral marketing on impulse buying in the marketplace marketplace (Study on Postgraduate Students at Lambung Mangkurat University). 2) There is a significant effect partially on price on impulsive purchases in the marketplace marketplace (Study on Postgraduate Students at Lambung Mangkurat University). 3) there is a significant simultaneous effect of viral marketing and price on impulse buying in the marketplace marketplace (Study on Postgraduate Students at Lambung Mangkurat University). Keywords : Viral Marketing, Price, Impulse Buying